ASSESSMENT OF PORT CITY SERVICE CENTER ALIGNMENT IN THE TERRAIN - Sri Rejeki; Abdi Sugiarto; Abdiyanto; Cut Nuraini; Feby Milanie (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2024)
Medan, in North Sumatra, is growing rapidly, especially in the sub-districts of Medan Marelan and Medan Belawan, where urban activities and population movement are increasing. As a result, North Medan has been designated as the City Service Centre (CSC) of Medan City, with CSC Labuhan in Medan Labuhan sub-district playing a major role. This highlights the importance of Medan Labuhan in providing essential services and infrastructure to support the growth of the area. In order to effectively serve the community, it is important to ensure that CSC Labuhan meets the area's needs and standards for a city service center. Aims: The objective of this research is twofold: first, to determine the status of the service center system in North Medan; and second, to evaluate the suitability of CSC Labuhan's functions in serving the North Medan region. Methodology and results: The research method is descriptive analysis using both quantitative data and qualitative information. This is achieved through the use of scalogram analysis, centrality index analysis and rank-size rule analysis. Conclusion, significance and implication: The results indicate that the optimal locations for urban service centers are in Sub-District Besar (Medan Labuhan subdistrict), Subdistrict Rengas Pulau (Medan Marelan subdistrict), and Subdistrict Belawan I (Medan Belawan subdistrict). Conversely, Medan City RTRW 2022-2042 designates Labuhan CSC as Subdistrict Pekan Labuhan.